1999
DOI: 10.1007/s002239900712
|View full text |Cite
|
Sign up to set email alerts
|

Limited Clinical Utility of a Self-Evaluating Risk Assessment Scale for Postmenopausal Osteoporosis: Lack of Predictive Value of Lifestyle-Related Factors

Abstract: The aim of this study was to assess the efficiency of a self-administered questionnaire to identify subjects with postmenopausal osteoporosis in the setting of first line medical care. A sample of 300 postmenopausal women completed the questionnaire based on 18 items. Bone mineral density at the lumbar spine (BMD-L), total hip (BMD-H), and femoral neck (BMD-N) was used as objective criterion for evaluation. The mean risk score was 8.2 +/- 3.21. BMD was correlated with total risk score: r = -0.32 for BMD-L, -0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…37 These findings are consistent with earlier studies of white and Asian women that reported that age and weight were important predictors of BMD, and that indices based on age and weight performed as well as models that included additional variables. [18][19][20][21][22]35,38 In fact, the algorithm for calculating OsteoRisk risk for osteoporosis developed in the current study is exactly the same as the algorithm developed independently for the OST and the OSTA, which was originally developed in an Asian cohort and later validated in white cohorts. [18][19][20]35 The OsteoRisk cutoffs for defining high, medium, and low risk are slightly different from those reported for the OST, which may in part reflect ethnic or cultural differences of Latin American versus North American and European populations.…”
Section: Discussionmentioning
confidence: 99%
“…37 These findings are consistent with earlier studies of white and Asian women that reported that age and weight were important predictors of BMD, and that indices based on age and weight performed as well as models that included additional variables. [18][19][20][21][22]35,38 In fact, the algorithm for calculating OsteoRisk risk for osteoporosis developed in the current study is exactly the same as the algorithm developed independently for the OST and the OSTA, which was originally developed in an Asian cohort and later validated in white cohorts. [18][19][20]35 The OsteoRisk cutoffs for defining high, medium, and low risk are slightly different from those reported for the OST, which may in part reflect ethnic or cultural differences of Latin American versus North American and European populations.…”
Section: Discussionmentioning
confidence: 99%
“…Decision aids based on regression models 18 or involving detailed questionnaires 19 were excluded from this analysis. Our search identified 4 decision rules for BMD testing.…”
Section: Inclusion Of Decision Rules For Referring Women For Bone Denmentioning
confidence: 99%
“…prolonged corticosteroid therapy), an underlying medical condition such as rheumatoid arthritis, and other factors such as low-trauma fracture. As osteoporotic fracture risk is also related to components of bone that are not captured by measuring BMD, as well as to non-skeletal risk factors over and above BMD, 9,33 on an individual basis these risk factors might still be relevant and appropriate selection criteria for the identification of at-risk patients. Therefore, to best guide pharmacists with counselling and in directing appropriate pharmacological treatment, factors such as medication use, medical conditions and history of low-trauma fracture should be incorporated into the risk assessment.…”
Section: Probability and Risk Indexmentioning
confidence: 99%